Understanding stigma: The experiences of people with drug-sensitive pulmonary tuberculosis in Rawalpindi, Pakistan. - Ruby Stein; Anil Fastenau; Hina Aman; Nimer Ortuño-Gutiérrez; Chris Schmotzer; Sophie Cw Unterkircher; Eva Pilot (PLoS ONE)
Introduction Tuberculosis (TB) is a major global health problem and Pakistan is ranked fifth among the 30 high-burden countries in the world. TB-related stigma affects health seeking behaviour and treatment adherence, increasing disease transmission and worsening health outcomes. This study aimed to explore experiences of stigma among people with TB (PWTB) in Rawalpindi to help inform targeted stigma reduction interventions that could improve health seeking behaviour, treatment adherence and the mental well-being of PWTB in Pakistan. Methodology In-depth interviews were conducted with 15 people with pulmonary drug sensitive TB from Rawalpindi, Pakistan. For assessing emerging themes, an inductive themed analysis approach was used. Next, a deductive approach was applied by analysing and interpreting the data against the Health Stigma and Discrimination Framework. Results TB- related stigma among participants was driven by fear of infection, which in some cases was due to misconceptions surrounding TB transmission as well as social judgement and gender norms. Stigma manifested through: anticipated and perceived stigma in the form of non-disclosure and fear of social exclusion; enacted stigma among friends and family, in the workplace and healthcare settings; and internalised stigma, The negative outcomes of stigma that resulted for some participants included non- adherence and social exclusion, in the form of loss of marriage prospects and employment. Conclusion This study confirms that TB-related stigma persists in Pakistan, impacting he well-being, medication adherence and treatment outcomes of PWTB. The distinct drivers, manifestations and outcomes of stigma in Rawalpindi Pakistan uncovered from this study, supported by previous research, can help inform targeted stigma reduction interventions such as public education programmes.